2019
DOI: 10.1556/2006.8.2019.01
|View full text |Cite
|
Sign up to set email alerts
|

The association between problematic online gaming and perceived stress: The moderating effect of psychological resilience

Abstract: Background and aims: Vulnerability to stress appears to be a potential predisposing factor for developing specific internet-use disorders, such as Internet Gaming Disorder (IGD). Studies investigating the protective effect of psychological resilience against the impact of perceived stress on IGD and weekly gameplay have yet to be reported in the existing literature. The aim of this study was to examine the potential moderating relationships between perceived stress and online gaming (more specifically operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 43 publications
8
65
3
1
Order By: Relevance
“…Moreover, internet gaming disorder was included in Section III of the DSM-5 as a condition for further study. Internet gaming disorder was said to originate as a coping mechanism against stress (53), and stress reduction was identified as an important motivational driver of excessive online gaming (54,55). In a recent study, about half of the studied student sample reported that their gaming behavior had increased during the COVID-19 lockdown period and that gaming behavior was associated with examination-related stress (56).…”
Section: Psychological Consequences Of Covid-19 On Individuals With Amentioning
confidence: 99%
“…Moreover, internet gaming disorder was included in Section III of the DSM-5 as a condition for further study. Internet gaming disorder was said to originate as a coping mechanism against stress (53), and stress reduction was identified as an important motivational driver of excessive online gaming (54,55). In a recent study, about half of the studied student sample reported that their gaming behavior had increased during the COVID-19 lockdown period and that gaming behavior was associated with examination-related stress (56).…”
Section: Psychological Consequences Of Covid-19 On Individuals With Amentioning
confidence: 99%
“…Furthermore, resilience was reportedly lower among adolescents with IGD according to questionnaire assessments [15]. Its moderating role in the association between stress and IGD severity was demonstrated by an online questionnaire survey [23]. However, the difference in resilience was not evaluated among adults with IGD based on diagnostic interviewing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference in resilience was not evaluated among adults with IGD based on diagnostic interviewing. Further, resilience included a variety of personal characteristics, such as acceptance, problem-solving skills, capacity to recover, self-regulation, personal competence, and self-efficacy [23,24]. Which characteristics of resilience plays an important role involving development of IGD and should be intervened firstly has not been well-evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies report the symptom severity of GD to be associated with increased perceived stress [78][79][80][81][82][83] and emotional trauma or maltreatment during childhood [84,85]. Furthermore, Canale et al [79] could show that stress was positively correlated with hours of game play per week. As known from substance use disorder neuroscience, altered stress processing may be associated with neural alterations in the brain's stress system which includes executive control and reward networks [86].…”
Section: Neuroscientific and Psychological Findings On Stress In Gdmentioning
confidence: 99%
“…Stress reduction and stress control have been deployed as parts of selective intervention programs for GD and Internet use disorder to school students [30••]. In addition, reduced resilience and self-control have been identified as mediators between stress and problematic gaming behavior [79,92], and thus might have protective effects.…”
Section: How To Include Stress Reduction Techniques Into Prevention Amentioning
confidence: 99%